Advances in Biomaterials for Biomedical Applications - Tripathi, Anuj; Melo, Jose Savio (Advanced Structured Materials,, 2017)
This book highlights recent advances in the field of biomaterials design and the state of the art in biomaterials applications for biomedicine. Addressing key aspects of biomaterials, the book explores technological advances at multi-scale levels (macro, micro, and nano), which are used in applications related to cell and tissue regeneration. The book also discusses the future scope of bio-integrated systems. The contents are supplemented by illustrated examples, and schematics of molecular and cellular interactions with biomaterials/scaffolds are included to promote a better understanding of the complex biological mechanisms involved in material-to-biomolecule interactions. The book also covers factors that govern cell growth, differentiation, and regeneration in connection with the treatment and recovery of native biological systems. Tissue engineering, drug screening and delivery, and electrolyte complexes for biomedical applications are also covered in detail. This book offers a comprehensive reference guide for multi-disciplinary communities working in the area of biomaterials, and will benefit researchers and graduate students alike.